Comment on the report "Operational Earthquake Forecasting" by the International Commission on Earthquake Forecasting for Civil Protection - Stuart Crampin (Annals of Geophysics, 2012)
The recently published report Operational Earthquake Forecasting: State of Knowledge and Guidelines for Utilization by the International Commission on Earthquake Forecasting for Civil Protection (ICEF) presupposes that there is no method for the short-term prediction of large earthquakes that has been demonstrated to be both reliable and skillful. This is no longer correct. Earthquakes can be deterministically stress-forecast by using shear-wave splitting to monitor stress-accumulation in the rock mass surrounding the earthquake source. This new understanding of fluid-rock deformation means that the recommendations of the ICEF Report are no longer appropriate. This comment reviews this new understanding and suggests that the way forward for operational earthquake forecasting in Italy is to install one or more controlled-source three-borehole Stress-Monitoring Sites and use shear-wave splitting to monitor stress-accumulation and stress-forecast all damaging (M ≥ 5) earthquakes in Italy.